Faktor-Faktor Mempengaruhi Profitabilitas Bank di Bursa Efek Indonesia - Awinda Juliantri Krismonika; Aris Munandar; Vhika Meiriasari (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
This study aims to analyze the effect of cash flow from operating activities, loan to deposit ratio, non-performing loans, and return on assets on net interest margins in banks listed on the Indonesia Stock Exchange in 2015-2019. Data is obtained from the IDX website for the 2015- 2019 period for financial service companies listed on the Indonesia Stock Exchange in the 2013-2017 periods. The data were analyzed using multiple regression methods which were processed using Eviews. The results of the investigation indicates that partially each cash flow from operating activities, loan to deposit ratio, and non-performing loans has a significant and negative effect on the net interest margin. Furthermore, return on assets has a significant and positive effect on net interest margin. Simultaneously, operating cash flow, loan to deposit ratio, and non-performing loan, return on assets have a significant and positive effect on Net Interest Margin. This study provides information to companies in the financial sector to pay attention to operating activity cash flow factors, loan to deposit ratios, and non-performing because these factors affect the net interest margin